Influência do excesso de lítio nas propriedades estruturais e ópticas de LiBaPO4 dopados com íons lantanídeos - Hora, Daniela Alves (2022)
In this work, we investigated the effect of Li excess on the properties of pure and trivalent lanthanides (Eu3+ or T3+) doped LiBaPO4. LiBaPO4 were prepared by the Sol-gel route using polyvinyl alcohol (PVA) and glucose as a polymerizing agent. The hexagonal phase of LiBaPO4 was confirmed by X-Ray Diffractometry (XRD). The cristallite size were calculated at the nanometer scale (17–39 nm). The Li+ excess did not influence the linear shape on the particle size. PL results revels Eu exhibits an intense emission at 464 nm (green region) attributed to Eu2+ and another region referring to Eu3+ at red region (616 nm). For LiBaPO4:Tb3+, there is a very intense excitation in the UV region (223 nm) and consequently later emission spectra, in the green region (546 nm). For Tb dopant, however, the Li+ excess no contributes significantly to the highest emission (546 nm). On the other hand, the Li+ excess contribute to the reduction of Eu3+→Eu2+, as well as for the stabilization of Eu2+ in the compound, as verified by XEOL measurements at the LIII - edge. XANES spectra attributed its strong absorption (6977 eV) to Eu3+, confirming thatLi+ did not affect the established valence of Eu.